Alpha oscillations reveal implicit visual processing of motion in hemianopia. (January 2020) - Grasso, Paolo A.; Pietrelli, Mattia; Zanon, Marco; Làdavas, Elisabetta; Bertini, Caterina
Abstract: After lesion or deafferentation of the primary visual cortex, hemianopic patients experience loss of conscious vision in their blind field. However, due to the spared colliculo-extrastriate pathway, they might retain the ability to implicitly process motion stimuli through the activation of spared dorsal-extrastriate areas, despite the absence of awareness. To test this hypothesis, Electroencephalogram (EEG) was recorded from a group of hemianopic patients without blindsight (i.e., who performed at chance in different forced-choice tasks), while motion stimuli, static stimuli or no stimuli (i.e., blank condition) were presented either in their intact or in their blind visual field. EEG analyses were performed in the time-frequency domain. The presentation of both motion and static stimuli in the intact field induced synchronization in the theta band and desynchronization both in the alpha and the beta band. In contrast, for stimuli presented in the blind field, significantly greater desynchronization in the alpha range was observed only after the presentation of motion stimuli, compared to the blank condition, over posterior parietal-occipital electrodes in the lesioned hemisphere, at a late time window (500–800 msec). No alpha desynchronization was elicited by static stimuli. These results show that hemianopic patients can process only visual signals relying on the activation of the dorsal pathway (i.e., motion stimuli) in the absence of awareness and suggest different patterns of electrophysiological activity for conscious and unconscious visual processing. Specifically, visual processing in the absence of awareness elicits an activity limited to the alpha range, most likely reflecting a "local" process, occurring within the extrastriate areas and not participating in inter-areal communication. This also suggests a response specificity in this frequency band for implicit visual processing. In contrast, visual awareness evokes changes in different frequency bands, suggesting a "global" process, accomplished by activity in a wide range of frequencies, probably within and across cortical areas.